66.091 Kimyo va kimyoviy texnologiyalar: STUDYING ISOTHERMS OF ADSORPTION AND DESORPTION OF NITROGEN ON A SORBENT SYNTHESIS FOR SELECTIVE EXTRACTION OF LITHIUM - Yusupov, Muzafar; Akhmadjanov, Ibrokhim; Djalilov, Abdulakhat; Karimov, Mas’ud (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Objective. The purpose of this work is to study the adsorption characteristics of a synthesized organoelement sorbent intended for the sorption of lithium from brines, based on the adsorption and desorption isotherm of nitrogen at 77.35°K. Determination of the main adsorption characteristics of sorbents such as specific surface area, monolayer capacity, specific volume, average pore width, etc. All calculations were performed based on the BET method. The specific surface area of the sorbent is determined in two ways, i.e. by mass and volume of adsorbate gas using linear forms of the BET equation. The results of the nitrogen desorption isotherm on the synthesized sorbent according to the BJH method are presented. Methods. To achieve the goal of this study, the standard method for determining the specific surface area of adsorbents was used - the BET method and pore size distribution - the BJH method. To determine the specific surface area using the multipoint BET method, it is necessary to measure the equilibrium values of the mass of the adsorbed gas (in our case, nitrogen) per unit mass of the adsorbent for at least three different relative pressures. Results. The specific surface area of the sorbent, determined in two ways i.e. by mass and volume of adsorbate gas using the BET method was 4.99 m2/g. It was determined that the main capacity of the synthesized sorbent consists of pores with a width of 9 to 20 nm. The results of desorption based on the BJH method are presented. Conclusion. The adsorption characteristics of the synthesized sorbent for the selective extraction of lithium from brines were determined, such as specific surface area, monolayer capacity, pore width, etc. The results were obtained with a nitrogen adsorption isotherm at 77.35 °K. Using the BET equations, the specific surface area of the synthesized sorbent was determined, which was 4.99 m2/g. The calculated results are compared with the results obtained by the specific surface area analyzer.